2010
DOI: 10.4314/gjass.v8i2.51890
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal processing methods on the proximate composition, gross energy, minerals and ricin content of undecorticated castor oil seed (<i>Ricinus communis</i>)

Abstract: The nutritive value of raw and thermal processed castor oil seed (Ricinus communis) was investigated using the following parameters; proximate composition, gross energy, mineral constituents and ricin content. Three thermal processing methods; toasting, boiling and soaking-and-boiling were used in the processing of the seed as a way of improving its nutritive value. The three methods achieved a drastic reduction in the ricin levels. Toasting, boiling and soaking-and-boiling reduced ricin level by 93.05%, 94.84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 9 publications
4
14
0
3
Order By: Relevance
“…This result shows that birds on T 3 were poor converters of feed to dozen of egg, this might be due to the high residue of ricin in the toasted meal. Nsa (2008) reported decrease in egg production as ricin content in laying birds diet increased. The improved performance of the birds on diets containing other test ingredients other than toasted seed meal, suggested enhanced nutritive value which encouraged better utilization by laying birds and could be attributed to the better detoxification of the meal (table II), similar observations were recorded by Udedibie and Mba (1994); Amaefule and Obioha (1998);Finks et al (1992); Ukachukwu and Anugwa (1995); Nsa et al (2010) for pigeon pea, pigeon pea, cowpea, soybean and castor oil seed respectively.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…This result shows that birds on T 3 were poor converters of feed to dozen of egg, this might be due to the high residue of ricin in the toasted meal. Nsa (2008) reported decrease in egg production as ricin content in laying birds diet increased. The improved performance of the birds on diets containing other test ingredients other than toasted seed meal, suggested enhanced nutritive value which encouraged better utilization by laying birds and could be attributed to the better detoxification of the meal (table II), similar observations were recorded by Udedibie and Mba (1994); Amaefule and Obioha (1998);Finks et al (1992); Ukachukwu and Anugwa (1995); Nsa et al (2010) for pigeon pea, pigeon pea, cowpea, soybean and castor oil seed respectively.…”
Section: Resultsmentioning
confidence: 98%
“…However, Values obtained from all the treatment methods were higher than the 21.80, 22.50 and 22.39 percent crude protein levels reported for raw kidney bean, lima bean and pigeon pea respectively (Oyenuga, 1968;Okorie et al, 1985;Apata and Ologhobo, 1994;Ukachukwu and Obioha, 1997;Ukotebi, 2002). Nsa and Ukachukwu (2009) have shown that the crude protein value of castor oil seed meal ranks with those of green seed, bambara, groundnut seed, Mucuna cochinenensis, Milletia obanensis, but lower than that of groundnut and soybean seed meal which is the richest in crude protein value among the legume species (Ene-Obong and Carnovale, 1992;Apata and Ologhobo, 1994). This indicates that all the treatment methods retain adequate protein level as a good concentrate source for livestock feeds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Testa biji memiliki kandungan serat yang tinggi, kehilangan itu berarti merupakan penurunan kandungan serat kasar. Hal serupa telah dilaporkan oleh Nsa 19 . Sementara hasil penelitian Udensi, et.al 20 menyebutkan bahwa perlakuan perendaman yang diikuti dengan perebusan tidak memberikan pengaruh, kecuali pada perendaman selama 24 jam yang diikuti perebusan selama 90 menit memberikan hasil serat kasar paling rendah dibandingkan perlakuan lain, namun meningkatkan kandungan karbohidrat pada kacang kara benguk.…”
Section: Hasil Dan Pembahasan Kandungan Proksimat Tepung Biji Kapasunclassified